2019
DOI: 10.3390/su11154086
|View full text |Cite
|
Sign up to set email alerts
|

Is an Environment with High Biodiversity the Most Attractive for Human Recreation? A Case Study in Baoji, China

Abstract: Evidence has been accumulating of the psychological and physiological benefits and well-being gained by individuals from recreational activities in urban green spaces due to their ability to sustain biodiversity, but maximizing both biodiversity and recreational values of green spaces has become increasingly difficult in practice. In order to better maximize the biodiversity and recreational value of urban green space, this study was conducted through the utilization of an onsite questionnaire to understand pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 43 publications
1
11
1
Order By: Relevance
“…The results indicated that there was a significant relationship between certain PSDs and psychological restoration, and the PSDs that had significant predictive effects on psychological restoration varied across different types of environments. These findings support a previous study which found that the effects of the same PSDs varied with different environments due to different landscape characteristics and configurations [ 45 ].…”
Section: Discussionsupporting
confidence: 91%
“…The results indicated that there was a significant relationship between certain PSDs and psychological restoration, and the PSDs that had significant predictive effects on psychological restoration varied across different types of environments. These findings support a previous study which found that the effects of the same PSDs varied with different environments due to different landscape characteristics and configurations [ 45 ].…”
Section: Discussionsupporting
confidence: 91%
“…Dallimer et al, 2012;Fuller et al, 2007;Marselle et al, 2016). Studies report a good, general concordance between actual and perceived biodiversity (Fuller et al, 2007;Gao et al, 2019;Gonçalves et al, 2021;Johansson et al, 2014;Lindemann-Matthies et al, 2010;Meyer-Grandbastien et al, 2020;Simkin et al, 2021;Southon et al, 2018), yet the accuracy of lay people's biodiversity assessments does not allow for conflating both constructs (Austen et al, 2021;Dallimer et al, 2012). Compared with actual biodiversity, perceived biodiversity has been shown to be a stronger predictor of mental well-being (Cameron et al, 2020;Dallimer et al, 2012;Schebella et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies reporting a good agreement between perceived and actual diversity also allowed participants to directly compare environments (e.g. Gao et al, 2019;Johansson et al, 2014;Simkin et al, 2020;Southon et al, 2018), thus supporting the assumption that the study design might be a crucial factor that determines the accuracy of diversity ratings, and our understanding of perceived diversity.…”
Section: Association Between Perceived and Actual Diversitymentioning
confidence: 82%
“…Lately, there has been a growing interest in establishing the link between measured and perceived biodiversity to determine the accuracy of this proxy measure. Most studies confirm a relationship between both (Ferraro et al, 2020; Fuller et al, 2007; Gao et al, 2019; Gonçalves et al, 2021; Johansson et al, 2014; Lindemann-Matthies et al, 2010; Rozario et al, 2024; Southon et al, 2018) but associations are often weak (Rozario et al, 2024) or non-existent (Dallimer et al, 2012; Phillips & Lindquist, 2021; Stobbe et al, 2022). This indicates that, despite a substantial overlap, there is a divergence between biodiversity measured by biologists and how people perceive it.…”
Section: Introductionmentioning
confidence: 99%